Pengaruh Stres Kerja, Beban Kerja, dan Work Experience Terhadap Kinerja Karyawan - Trianika, Ayu Retno; Sumartik, Sumartik; Firdaus, Vera (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The fundamental components in hierarchical progress are human resources as the main driver and motivation as the mindset for running the organization. The increasing competition in the workplace has driven institutions or organizations to continuously innovate in their offerings, creating products or services that benefit society. The aim of this research is to understand how the performance of employees at PT. Pos Indonesia Sidoarjo is influenced by job stress, workload, and work experience both simultaneously and partially. This study employs quantitative research with multiple linear regression analysis in an associative research style. Data collection was conducted using a poll distributed through Google forms. The entire population of this study consisted of 86 employees from PT. Pos Indonesia Sidoarjo, with a sample of 55 respondents selected using purposive sampling. The results of the study can be concluded that employee performance is positively influenced by work stress, workload, and work experience at PT.Pos Indonesia Sidoarjo.